Small RNAs in Outer Membrane Vesicles and Their Function in Host-Microbe Interactions - Ahmadi Badi, Sara; Bruno, Stefania Paola; Moshiri, Arfa; Tarashi, Samira; Siadat, Seyed Davar; Masotti, Andrea (Frontiers in Microbiology, 2020)
Outer membrane vesicles (OMVs) produced by Gram-negative bacteria and their RNA content have recently received increasing attention as novel mediators of host-guest intercellular and interspecies communication. These kinds of vesicles allow not only the export of proteins, but also of DNA and other small RNAs. We previously reported that the production of bacterial vesicles could represent a way to communicate with the surrounding environment. This general mechanism, exploited by bacteria and viruses, allows conveying “messages” to the surrounding cells and tissues, thus leading to the manipulation of the host immune response. Many functions attributed to OMVs are a consequence of their high capability to survive in different environmental stressors and to enter into cells quite easily. As these properties can be exploited to advantage human health, in this review, we summarized the papers that reported the use of OMVs as modulators of cellular activities through the involvement of the RNAs contained within. We also discussed what has been done with OMVs and what remains to be discovered in order to prompt the investigations toward the complete elucidation of the role and functions of these vesicles.